Designing Raster Cells as the Basis for Developing Personal Graphic Language - Z. Vujić, Jana; Bernašek, Aleksandra; Koren, Tajana (Journal of Graphic Engineering and Design, 2023)
Continuous work in creating new designer solutions points towards the need to create personal routines as personal communication in the relation comprising design, algorithms, and original computer graphics. This paper shows procedures for developing a control language for creating graphic designs with individual raster elements (screening element obtaint by halftoning). Personal commands should set routines in a language understood by the printer and the designer. The PostScript basis is used because we mix vector and pixel graphics in the same program stream, as well as different colour systems, and our own raster forms. The printing raster is set with the target of special design multi-use, and this includes the field of security graphics and art computer reproduction. Each raster form assumes modifications, creating their raster family. The raster cell content is transformed with PostScript, allowing the setting of basic values, angle and liniature for each pixel separately. Raster cells are mixed in multi-colour graphics to the level of individual designs with variable values of parameters determining them.